CANTAI E MULTIPLICAI-VOS... : ESTUDO DA HARPA CRISTÃ COMO INSTRUMENTO DE EXPANSÃO DA MISSÃO NO PENTECOSTALISMO NO BRASIL (1910-1970) - Souza Junior, Milton Rodrigues de (2011)
This dissertation intends to study the Christian Harp, one of the main national protestant hymnals, looking to identify it as instrument of expansion in Brazil s Pentecostalism mission in the period between 1910 and 1970, while appreciating the history and the creation of this liturgical book, intending to comprehend its usage as motivational element in the missionary practice of the Brazilian Pentecostal churches. It also consists of knowing the characteristics of construction of this compendium, passing through the presentation of its hymnists profiles and through the assiduous study of its musical structure and literary composition, while being aware of some important constitutive characteristics that are used, such as the theological concepts. Looking for a missiology concept that shows to be more correlated with the theological content of this hymnal and the referral of various examples of incitement to the evangelist practice found within its songs, which leads to the comprehension of the relevancy of the Christian Harp in the liturgical life of confessional pentecostal churches in Brazil, and its bold presence as an efficient developer of missionary practice of these faith communities.